ENGLISH FUN LEARNING WITH DUOLINGO APPS FOR 11th SENIOR HIGH SCHOOL STUDENTS DURING THE COVID 19 PANDEMIC - Muhamad Sofian Hadi; Febrianti Ifdhal Prisantika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
This article aims to know the influence of using of Duolingo language learning apps and to know the student’s perception toward Duolingo application in teaching English. This study aims to improve students experience during learning English in COVID-19 pandemic particularly by using Duolingo as a self-learning, namely English Fun Learning with Duolingo Apps For 11th Senior High School During The Pandemic. As we knew that during the pandemic, the way of students’ learning and teaching becomes difficult and impractical so that students have to further improve their quality to learn better English. This study aims to narrate students experience during learning English in COVID-19 pandemic particularly by using Duolingo as a self-learning. This research used quantitative data. The quantitative data were collected from student’s questionnaire. The participants of this article were 8 students of XI MIPA 1 and 8 students of XI MIPA 2 from Dharma Karya UT Senior High School.